Antimicrobial resistance and virulence genes profiles of Arcobacter butzleri strains isolated from back yard chickens and retail poultry meat in Chile. (1st February 2021) - Vidal‐Veuthey, B.; Jara, R.; Santander, K.; Mella, A.; Ruiz, S.; Collado, L.
Abstract: This research aims to investigate the presence and pathogenic potential of Arcobacter in poultry meat samples purchased in the retail market of Valdivia (South of Chile) as well as in faecal samples from backyard chickens from rural areas around this city. The isolates obtained were identified by molecular methods. Furthermore, putative virulence genes were assessed by PCR and the antimicrobial resistance was tested by phenotypic methods. Arcobacter was present in 41·6% of the samples, with the highest value in retail poultry meat (55·7%) followed by backyard production (28·0%). Arcobacter butzleri was the most prevalent species (75·6%) followed by Arcobacter skirrowii (14·8%) and Arcobacter cryaerophilus (9·6%). An 8·5% of A. butzleri strains from meat were resistant to both ciprofloxacin and tetracycline and 6·1% were resistant to erythromycin, while none was resistant to gentamycin, unlike strains from domestic chickens, which showed no resistance. Furthermore, A. butzleri strains from chicken meat presented a higher prevalence of virulence genes than strains from domestic chickens. In fact, in this last group, some genes ( hecA, hecB and irgA ) were completely absent. Therefore, this study provides insight on the epidemiology of Arcobacter in Chilean poultry and suggests that under traditional breeding conditions strains are, apparently, less pathogenic and drug resistant. Significance and Impact of the Study: Arcobacter is considered an emergent foodborne enteropathogen. However, its prevalence in farm animals, as well as their virulence and antibiotic resistance, is partially known because most studies have been concentrated on industrialized production. This is mainly due to the fact that strains of arcobacters obtained from traditionally bred backyard poultry are generally not studied. Therefore, our results, in addition to updating the data on Arcobacter in poultry samples in Chile, suggest that under traditional breeding conditions strains are, apparently, less pathogenic and drug resistant that those found in retail poultry meat.